Development of Clarstatin, a Novel Drug Lead for the Therapy of Autoimmune Uveitis - Shira Merzbach; Amnon Hoffman; Philip Lazarovici; Chaim Gilon; Radgonde Amer (MDPI AG, 2024)
We describe the design, synthesis, and activity of a potent thiourea-bridged backbone cyclic peptidomimetic known as Clarstatin, comprising a 5-amino acid sequence (Q/D)1-(R/K)2-X3-X4-A5-(Gln/Asp)1-(Arg/Lys)2-AA3-AA4-Ala5-based on a motif called "shared epitope (SE)", specifically present in specific alleles of the HLA-DRB1 gene. This SE binds to a particular site within the proline reach domain (P-domain) of the cell surface-calreticulin (CS-CRT). CS-CRT is a multifunctional endoplasmic reticulum (ER) calcium-binding protein that is located on the cell surface of T cells and triggers innate immune signaling, leading to the development of inflammatory autoimmune diseases. The development of Clarstatin was based on the parent peptide W-G-D1-K2-S3-G4-A5- derived from the active region of the SE. Following the design based on the cycloscan method, the synthesis of Clarstatin was performed by the Fmoc solid phase peptide synthesis (SPPS) method, purified by HPLC to 96% homogeneity, and its structure was confirmed by LC-MS. Clarstatin reduced calcium levels in Jurkat lymphocyte cultures, ameliorated uveitis in vivo in the experimental autoimmune uveitis (EAU) mice model, and was safe upon acute toxicity evaluation. These findings identify Clarstatin as a promising lead compound for future drug development as a novel class of therapeutic agents in the therapy of uveitis.